Pengaruh Disiplin Kerja dan Beban Kerja terhadap Kinerja Karyawan PT Angkasa Pura I Bandar Udara Internasional Juanda - Ananda Husni Abdul Fathah; Sulastri Irbayuni (Universitas Batanghari Jambi, 2023)
The purpose of this study is to explain whether Work Discipline and Workload affect Employee Performance. This object is the company PT Angkasa Pura I Juanda Company. there are 7 departments taken as respondents based on the proportional sampling technique, namely the number of samples taken in each division or group as a representative according to the proportion. Therefore based on the sampling technique used from the entire population using the slovin formula, it is known that the sample used as respondents was 76 respondents. The type of data used is primary data, in the form of data directly from research sources, namely questionnaires distributed to each respondent at PT Angkasa Pura I Juanda, secondary data, in the form of data obtained from PT Angkasa Pura I Juanda, including attendance data, and also performance employees in general. The analysis technique used to validate the data hypothesis is SEM PLS. The results of the study prove that (1) Work Discipline has a positive effect on Employee Performance at PT Angkasa Pura I Juanda Company. (2) Workload has a negative effect on Employee Performance of PT Angkasa Pura I Juanda Company.